Industrialized Building System In Malaysia Construction Industry - Phon Chai, Priyanut (2013)
Malaysia is similar to any other developing country where consider the construction industry as one the main contributors to its Gross Domestic Product (GDP). Therefore the improvement of construction system from conventional approach which always arising unresolved issue such as delay to deliver the project, unnecessary wastage and less of sustainability practise shall be replaced by Industrialized Building System (IBS) which can resolve issue. However, this system is yet popular to our local construction industry even though it can provide many benefit which conventional approach is sort of. Industrialized Building System (IBS) is not ne2w to Malaysia and was introduced in the country over 50 years age. In addition, it has been continuously encouraging by the government, unfortunately the use of Industrialized Building System (IBS) is still far from the government target. A number barrier behind the adoption of this system are caused of unsuccessfully transform Industrialized Building System (IBS) as a primary choice method of construction in local construction industry. Therefore, based on the review on the available literature sources, this paper discussed the barriers and strategy aim of improvement the usage of industrialized building system (IBS) in Malaysia construction industry